Mixing particle production for relaxion mechanism - Klangburam T. (2023)
We consider the production of two heavy gauge bosons as a relaxation stopping mechanism. In this work, we analyse the conditions for a tachyonic mode for a linear combination of gauge bosons and show that the criteria are significantly different than the single gauge boson case. Moreover, the implementation of the mechanism on the U(1)′ model is demonstrated. We discuss various constraints for the relaxion mechanism. The phenomenology of the heavy gauge boson is also explored. We finally show a benchmark point of parameter space considering all constraints from relaxion and the U(1)′ mixing sector.